2016
DOI: 10.4238/gmr.15017548
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association study on early puberty in Bos indicus

Abstract: ABSTRACT. The aim of this study was to evaluate a genome wide association study (GWAS) approach to identify single nucleotide polymorphisms (SNPs) associated with fertility traits (early puberty) in Nellore cattle (Bos indicus). Fifty-five Nellore cows were selected from a herd monitored for early puberty onset (positive pregnancy at 18 months of age). Extremes of this phenotype were selected; 30 and 25 individuals were pregnant and non-pregnant, respectively, at that age. DNA samples were genotyped using a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…Using part of the data from the study of Hawken et al (2012), Fortes et al (2012) identified SNPs and chromosome regions that are directly associated with age at puberty of females and scrotal circumference in bulls. There have been some studies related to reproductive traits in zebu cattle such as: genome-wide association studies using 777k SNP panels (Irano et al, 2016;Nascimento et al, 2015;Costa et al, 2015), candidate gene/SNP studies (Fortes et al, 2013a,b), and combinations of methodologies (SNP association and gene expression; Fortes et al, 2014). The use of these technologies is being developed especially in tropical regions due to the importance of female performance in beef production profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Using part of the data from the study of Hawken et al (2012), Fortes et al (2012) identified SNPs and chromosome regions that are directly associated with age at puberty of females and scrotal circumference in bulls. There have been some studies related to reproductive traits in zebu cattle such as: genome-wide association studies using 777k SNP panels (Irano et al, 2016;Nascimento et al, 2015;Costa et al, 2015), candidate gene/SNP studies (Fortes et al, 2013a,b), and combinations of methodologies (SNP association and gene expression; Fortes et al, 2014). The use of these technologies is being developed especially in tropical regions due to the importance of female performance in beef production profitability.…”
Section: Introductionmentioning
confidence: 99%
“…RELL1 was found to exhibit a circadian expression pattern in hepatocytes in a manner that is controlled post-transcriptionally by a microRNA [14]. RELL1 was identified as a gene associated with a higher rate of stillborn fetuses in pigs [15], is also implicated in the age of fertility in cattle [16], collectively suggesting that RELL1 may influence reproductive traits in humans. Finally, RELL1 has been associated with a higher incidence of S. aureus nasal carriage in a community-based sample of Mexican-Americans in a Texas community [17].…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive rates in Bos indicus are generally lower than Bos taurus mainly due to delayed puberty and prolonged postpartum anestrus (Nascimento et al, 2016). Incidence of true postpartum anestrus varying from 11% to 38%in exotic (Peter et al, 2009) to as high as 53.15% in Indian cattle breeds (Kumar et al, 2014) was recorded.…”
mentioning
confidence: 96%